Publicysta w sporach dzienników opinii w Polsce. Analiza felietonów Rafała Ziemkiewicza w „Rzeczpospolitej” - Piątek, Paulina (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
Editors of daily newspapers struggle every day in order to attract readers. It applies especially to opinion newspapers which represent different political views. Two leading newspapers in Poland are “Rzeczpospolita” and “Gazeta Wyborcza”. The analysis of articles published in these newspapers shows how journalists are trying to manipulate the readers. The manipulation and persuassion, used by one of the leading commentators from “Rz” – Rafał Ziemkiewicz became the object of this study. Having almost 400 columns of that author’s analyzed, it can be stated that in his writings there are elements of both manipulation and persuassion. These elements are divided into thematic groups.